Ticks infesting humans in northern Misiones, Argentina - Lamattina, Daniela (2016)
This work presents records of ticks infesting humans in northern Misiones Province, Argentina. Also,notes on potential transmission of tick-borne pathogens are included. A total of 282 ticks attached to researchers were collected and identified by their morphological characters. Eight tick species were found: Amblyomma brasiliense, Amblyomma coelebs, Amblyomma dubitatum, Amblyomma incisum, Amblyomma ovale, Haemaphysalis juxtakochi, Rhipicephalus sanguineus and Rhipicephalus microplus. Some of these species as A. dubitatum, A. ovale and R. sanguineus have been found infected with spotted fever group rickettsiae pathogenic to humans in Brazil and Argentina. The potential role as vectors of humans pathogens of the ticks found attached to humans in this study is discussed.